2007
DOI: 10.1242/dev.009290
|View full text |Cite
|
Sign up to set email alerts
|

SHP-2 is required for the maintenance of cardiac progenitors

Abstract: The isolation and culturing of cardiac progenitor cells has demonstrated that growth factor signaling is required to maintain cardiac cell survival and proliferation. In this study, we demonstrate in Xenopus that SHP-2 activity is required for the maintenance of cardiac precursors in vivo. In the absence of SHP-2 signaling, cardiac progenitor cells downregulate genes associated with early heart development and fail to initiate cardiac differentiation. We further show that this requirement for SHP-2 is restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 92 publications
0
35
0
Order By: Relevance
“…Whole-mount antibody staining was performed as described previously (Goetz et al, 2006;Langdon et al, 2007Langdon et al, , 2012 with mouse antitropomyosin (Developmental Studies Hybridoma Bank, 1:10) and Alexa 568 anti-mouse [1:250, IgG (H+L)]. Embryos were then cleared in 2:1 benzyl benzoate:benzyl alcohol and imaged on a Leica MZ16F fluorescence microscope with a Qimaging Retiga 4000RV Fast1394 camera with QCapture software as well as a Zeiss 700 confocal microscope with MyZen software.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Whole-mount antibody staining was performed as described previously (Goetz et al, 2006;Langdon et al, 2007Langdon et al, , 2012 with mouse antitropomyosin (Developmental Studies Hybridoma Bank, 1:10) and Alexa 568 anti-mouse [1:250, IgG (H+L)]. Embryos were then cleared in 2:1 benzyl benzoate:benzyl alcohol and imaged on a Leica MZ16F fluorescence microscope with a Qimaging Retiga 4000RV Fast1394 camera with QCapture software as well as a Zeiss 700 confocal microscope with MyZen software.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…two independent rounds of injections) except for stage 33, which was conducted four independent times. Results are reported as the ratio of triple to double positive cells ± two standard deviations by Student's t-test as previously described (Goetz et al, 2006;Langdon et al, 2007).…”
Section: Mitotic Index and Apoptosismentioning
confidence: 99%
“…All experiments on embryos were conducted as reported previously (Goetz et al, 2006;Langdon et al, 2007). Densitometry was used to standardize loading levels in western blot analysis.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compared with other higher vertebrate models, Xenopus embryos can survive for longer without a properly functioning heart or circulatory system, enabling the observation of later consequences of cardiac malfunction. Moreover, the Xenopus model allows for tissue explantation for study in isolation (Afouda and Hoppler, 2009;Langdon et al, 2007;Raffin et al, 2000), as well as microinjection of overexpression constructs and antisense morpholino oligonucleotides to manipulate gene function (Brown et al, 2007;Brown et al, 2005;Christine and Conlon, 2008;Sive et al, 2000;Tada et al, 1997;Tandon et al, 2012). Crucially, studies have demonstrated a direct correlation between depleting cardiac proteins in Xenopus to that of genetic mutations in mouse or in human CHD patients (Kaltenbrun et al, 2011).…”
Section: Cardiac Profilingmentioning
confidence: 99%